The {omega}-3 fatty acid eicosapentaenoic acid elicits cAMP generation in colonic epithelial cells via a "store-operated" mechanism. - Roy, J; Lefkimmiatis, K; Moyer, M; Curci, S; Hofer, A (2010)
Eicosapentaenoic acid (EPA) is an omega-3 polyunsaturated fatty acid abundant in fish oil that exerts a wide spectrum of documented beneficial health effects in humans. Because dietary interventions are relatively inexpensive and are widely assumed to be safe, they have broad public appeal. Their endorsement can potentially have a major impact on human health, but hard mechanistic evidence that specifies how these derivatives work at the cellular level is limited. EPA (50 microM) caused a small elevation of cytoplasmic Ca(2+) concentration ([Ca(2+)]) in intact NCM460 human colonic epithelial cells as measured by fura 2 and a profound drop of [Ca(2+)] within the endoplasmic reticulum (ER) of permeabilized cells as monitored by compartmentalized mag-fura 2. Total internal reflection fluorescence microscopy showed that this loss of ER store [Ca(2+)] led to translocation of the ER-resident transmembrane Ca(2+) sensor STIM1. Using sensitive FRET-based sensors for cAMP in single cells, we further found that EPA caused a substantial increase in cellular cAMP concentration, a large fraction of which was dependent on the drop in ER [Ca(2+)], but independent of cytosolic Ca(2+). An additional component of the EPA-induced cAMP signal was sensitive to the phosphodiesterase inhibitor isobutyl methylxanthine. We conclude that EPA slowly releases ER Ca(2+) stores, resulting in the generation of cAMP. The elevated cAMP is apparently independent of classical G protein-coupled receptor activation and is likely the consequence of a newly described "store-operated" cAMP signaling pathway that is mediated by STIM1.